A Clinical Study Of Post Operative Refraction In Pciol Patients - Dr.R.Sasya M.S., Dr.A.P.R.Naidu M.S, Dr.M.V.Bhavani M.S , Dr.V.Murali Krishn (International Journal of Scientific Research and Management (IJSRM), 2015)
Contract is the cause of preventable blindness worldwide,with the developing world around three quarters of this blindness.Oneof the routinely done surgery in ophthalmic faculty is cataract operation. The purpose of cataract extraction with PC IOL (posteriorchamber intra ocular lens) implantation is to restore the patient's vision as much and as fast as possible. Such visual rehabilitation involvesthe correction of significant preoperative astigmatism and refractive error and the avoidance of post operative astigmatism, which maymake the prescription of post operative glasses very difficult and even binocular vision impossible